Contribution to the Sedge and Grass Flora of Gujarat - Desai, Rinku J.; Raole, Vinay M. (Indian Forester, 2013)
Diversity of grasses and sedges forms the major component of the forest. Field studies of the south Gujarat forest during last 3 years authors have collected 6 grasses and 2 sedges which were found to be noteworthy specimens. At the same time two grasses were collected after 50-100 years.